Применение методов статистического анализа при обработке опытных данных - Сидоренко, Анна Юрьевна; Мазманишвили, Александр Сергеевич (НТУ "ХПИ", 2013)
The typical problems of mathematical statistics, related to correlated sequences (to time counts) with a given fixed level of statistical correlation between them, are considered. The analytic expressions featuring distributions Chi-Squared's ones in the case of correlated counts are obtained. The charts of functions and distributions Chi-Squared's in the case of correlated counts are introduction.
Keywords: данные статистические; хи-квадрат; отсчеты коррелированные; плотность распределения; функция распределения